HUBUNGAN PENGETAHUAN IBU MENYUSUI TENTANG ASI EKSKLUSIF DENGAN PEMBERIAN MAKANAN PRELAKTEAL PADA NEONATUS DI RSUD GUNUNG TUA TAHUN 2023 - nasution, nur arfah; Harahap, Nur Hamima; Pane, Mustika Sari Dewi (Universitas Aufa Royhan, 2023)
Exclusive breastfeeding in infants is a necessity in meeting nutritional requirements. One of the factors causing the failure of exclusive breastfeeding is feeding Prelakteal. This study aims to determine the relationship of knowledge about breastfeeding Exclusive breastfeeding mothers with feeding prelakteal Neonatal RSUD Gunungtua. Penelitian Gunungtua using Correlational descriptive method. Its population is Nursing Mothers who have 0-28 day visit to the RSUD Gunungtua in 2023 as many as 35 people and sample technique used is total sampling Analysis of the data used by the Chi-square test with significance level test 0,05. Hasil chi-square value obtained p = 0.01 means that there is a relationship of knowledge about breastfeeding Exclusive breastfeeding mothers with feeding at RSUD prelakteal Neonatal Gunungtua in 2023. It is expected to further enhance the RSUD Gunungtua health promotion of exclusive breastfeeding in improving public health.